Linewidth enhancement factor and modulation bandwidth of lattice matched 1.5 micron InGaAsN/GaAs quantum well lasers - DONEGAN, JOHN (SPIE, 2004)
The linewidth enhancement factors of lattice-matched 1.5 ?m wavelength InGaNAs/GaAs and InGaAs/InP singlequantum- well structures have been calculated using microscopic theory including many-body effects and a 10x10 effective-mass Hamiltonian. For applications which require high gain and carrier densities, InGaNAs/GaAs quantum wells have a much lower linewidth enhancement factor over a temperature range 300?400 K than InGaAs. The linewidth enhancement factor of InGaNAs is almost independent of both carrier density and temperature compared with InGaAs. The small-signal modulation characteristics of these 1.5?m lattice-matched structures and their temperature dependence have also been calculated. It is found that the maximum bandwidth of the InGaNAs/GaAs quantum well lasers is about 2.3 times larger than that of the InGaAs/InP quantum well lasers due to the high differential gain. The slope efficiency for the 3dB bandwidth as a function of optical density is twice as large for InGaNAs/GaAs as for InGaAs/InP quantum well lasers.
Proceedings of SPIE
Semiconductor Lasers and Laser Dynamics
PUBLISHED
Strasbourg, France
Keywords: InGaAsN materials; Semiconductor quantum wells; linewidth enhancement factor; small signal